Recombinant human enterovirus 71 in hand, foot and mouth disease patients - Chan, Y.F.; AbuBakar, Sazaly (2004)
Two human enterovirus 71 (HEV71) isolates were identified from hand, foot and mouth disease patients with genome sequences that had high similarity to HEV71 (greater than or equal to93) at 5'UTR, P1, and P2 and coxsackievirus A16 (CV-A16, greater than or equal to85) at P3 and 3'UTR. Intertypic recombination is likely to have occurred between HEV71 and CV-A16 or an as-yet to be described CV-A16-like virus.